Intraosseous Ganglion of the Distal Tibia: Clinical, Radiological, and Operative Management - Sedeek Mohamed Sedeek; Q. Choudry; S. Garg (Case Reports in Orthopedics)
Intraosseous ganglia are benign cystic lesions located in the subchondral bone. Intraosseous ganglion cysts of the ankle are relatively uncommon. We present a case of recurrent intraosseous ganglion in the ankle of a 41-year-old female who had recurrence after initial surgery. She was treated effectively by curettage and autogenous cancellous bone grafting. At the final follow-up, satisfactory results were obtained with no recurrence or complications.